THE ALGORITHMS AND PROGRAMS OF DYNAMIC CALCULATION OF PARALLEL ROBOTS - Khôi, Phan Bùi (Vietnam Journal of Science and Technology, 2012)
SUMMARY The paper presents algorithms and programs of kinematic and dynamic calculation of parallel robots. The presented methods are effective and convenient for researching a lot of models of parallel robots